Factors affecting the use of electronic commerce from the point of view of the Saudi consumer in Al-qunfudah Governorate - Alzele, Frag Hassen (Journal of Economic, Administrative and Legal Sciences, 2020)
The current study aims to identify the factors which impact using of e-commerce from the point of view of the Saudi consumer, the researcher relied upon the descriptive-analytical method as a proper method for this study, whereas the effective factors on e-commerce were described and analyzed data and private information of the research sample from the consumers at Al-Qunfudah Governorate, the study sample consisted of (100) consumers from the study community with total numbers (350) consumers and the researcher relied upon the random sample to assure the inclusivity of distribution the questionnaire to the study community, and he relied upon a form of the questionnaire as the main tool to collect the private data of this study.The important outcomes which the study reached are the existence of a positive effect with a statistical significance between all of the safety and privacy and the readiness of the companies and usage of e-commerce, and the important recommendations of this study were: the necessity to bind the communications companies to increase the means of safety and privacy on the internet, whereas this leads the dealers' fee of safety in practicing e-commerce, in addition to work to develop the means of communication and internet to publish e-commerce.
Keywords: e-commerce; trust in electronic transactions; demographic characteristics